2006
DOI: 10.4086/cjtcs.2006.002
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We consider the dihedral hidden subgroup problem as the problem of distinguishing hidden subgroup states. We show that the optimal measurement for solving this problem is the so-called pretty good measurement. We then prove that the success probability of this measurement exhibits a sharp threshold as a function of the density ν = k/ log 2 N , where k is the number of copies of the hidden subgroup state and 2N is the order of the dihedral group. In particular, for ν < 1 the optimal measurement (and hence any m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Further Ip showed that for the dihedral hidden subgroup problem, the optimal measurement was not to perform a quantum Fourier transform over the dihedral group followed by a projective measurement. Continuing on in this line of inquiry, Bacon, Childs, and van Dam derived an exact expression for the optimal measurement for the dihedral hidden subgroup problem [19]. This measurement turned out to be the so-called pretty good measurement [43].…”
Section: The Hidden Subgroup Problemmentioning
confidence: 98%
See 3 more Smart Citations
“…Further Ip showed that for the dihedral hidden subgroup problem, the optimal measurement was not to perform a quantum Fourier transform over the dihedral group followed by a projective measurement. Continuing on in this line of inquiry, Bacon, Childs, and van Dam derived an exact expression for the optimal measurement for the dihedral hidden subgroup problem [19]. This measurement turned out to be the so-called pretty good measurement [43].…”
Section: The Hidden Subgroup Problemmentioning
confidence: 98%
“…Thus, even though measurement on a single register containing the hidden subgroup state is enough to information theoretically reconstruct the hidden subgroup state, a measurement across many registers containing the hidden subgroup is optimal for solving this problem. Unfortunately, it is not known how to efficiently implement the optimal measurement described in [19]. However, building upon the optimal measurement approach, Bacon, Childs, and van Dam then applied the apparatus of optimal measurements for the HSP to the HSP for certain semidirect product groups of the for Z r p ⋊ Z, for a fixed r and prime p [14].…”
Section: The Hidden Subgroup Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The set of measurements described in this way contains instances which are neither projective nor can they be obtained by combining projective measurements. This class of genuinely nonprojective measurements can be utilized, for example, in quantum computing [1,2], quantum cryptography [3,4], randomness certification [5], and quantum tomography [6]. But since genuinely nonprojective measurements cannot be combined from projective measurements, their experimental implementation is difficult and typically requires control over additional degrees of freedoms [7].…”
Section: Introductionmentioning
confidence: 99%